OFLOXACIN-INDUCED VASCULITIS - (:unkn) unknown (JAPAN SOC INTERNAL MEDICINE, 1995)
We describe a patient with hypersensitivity vasculitis due to ofloxacin therapy; the vasculitis was associated with elevated transaminase and IgA levels. Cyclophosphamide and intravenous pulse prednisolone resulted in clinical improvement.
Keywords: VASCULITIS; OFLOXACIN